Expression and characterization of recombinant trehalose synthase in Bacillus subtilis - Trieu, Nguyen Ngoc; Quynh, Nguyen Thi; Hoang, Nguyen Duc; Dat, Nguyen Manh; Long, Tran Duc; Loan, Nguyen Thi Hong (Academia Journal of Biology, 2020)
Trehalose synthase (TreS, EC 2.4.1.245) is a potential catalyst for synthesis of trehalose, an important natural disaccharide. In this study, the treS gene of Pseudomonas putida (VTCC 12263) was cloned into pHT01 plasmid at BamHI-XbaI position, expressed in Bacillus subtilis (B. subtilis) 1012, and characterized. The recombinant TreS had molecular weight of 68 kDa when fused with 8xHis tag at the C-terminus. catalyzed conversion of maltose to trehalose in optimal conditions had specific activity of 1.664 U/g. Expression of TreS was highest when B. subtilis 1012 harboring pHT01-treS was cultured in TB medium at 30 oC, induced with 1.0 mM IPTG when OD600 reached 0.8 and harvested after 10 hours of induction. The recombinant TreS purified by Ni-sepharose chromatography had specific activity of 41.700 U/g and formed a single band on Western blot with monoclonal antibody against His-tag. The recombinant TreS had optimal activity at 37 oC in 100 mM pH 7.4 PBS and 300 mM maltose. It was inhibited by NaCl, KCl and MgCl2 (retaining 45% or 75% specific activity in buffer containing 5 mM KCl or 5 mM MgCl2, respectively) and stimulated by imidazol (with specific activity increasing by 30–200%).